TOTAL OF ERYTHROCYTES, HAEMATOCRIT, AND HAEMOGLOBIN CHANGES OF Pangasius hypophthalmus THAT WERE IMMERSED IN CURCUMIN EXTRACT AND THAT WERE IN INFECTED BY Aeromonas hydrophila - Sarah Pabiola Saragih; Henni Syawal; Morina Riauwaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on June until September 2015 at Parasite and Fish Disease Laboratory, Faculty of Fisheries and Marine Science, University of Riau. The aims of this research was to know the blood changes (total of erythrocytes, haematocrit, and haemoglobin) of Pangasius hypophthalmus that were immersed in curcumin extract and that were infected by Aeromonas hydrophila. This research use Completely Randomized Design (CRD) with one factor, five treatments and three raplications. The treatments was immersion curcumin extract with different dose i.e : Kn (without immersed with curcumin extract and without infected by Aeromonas hydrophila); Kp (without curcumin extract and infected by Aeromonas hydrophila); P1, P2, and P3 immersed with curcumin extract ; 0.5 g/L ; 0.7 g/L ; 0.9 g/L. Immersed with curcumin extract was done by 2 minutes every 1 week and repeated during 4 weeks and infected by A. hydrophila in day 30 with intramuscular method.The result showed that immersed with curcumin extract on Pangasius hypopthalmus of treatment P3 on the best dose ( total of erythrocytes 3.00 x 106 sel/mm3 , haematocrit 27% and haemaglobin 9.47 g/dl).Keywords : Curcumin extract, Pangasius hypophthalmus, Aeromonas hydrophila, haematocrit and haemoglobin